Evaluation of the Efficacy of Stem Cell Therapy in Ovariectomized Osteoporotic Rats Based on Micro-CT and Dual-Energy X-Ray Absorptiometry: A Systematic Review and Meta-Analysis - Zhencheng Xiong; Ping Yi; Jialiang Lin; Shengfeng Qiu; Li Shu; Chi Zhang (Stem Cells International)
Objective. Osteoporosis is an abnormal bone metabolism disease characterized by microstructural degeneration of bone tissue and reduction in bone mass, resulting in increased brittleness of bone tissue and susceptibility to fracture. Due to the tissue regenerative potential of stem cell transplantation, it is now used in the treatment of various disease models such as osteoporosis. The purpose of this work is to carry out a systematic review and meta-analysis of the efficacy of stem cell therapy in ovariectomized (OVX) osteoporotic rats. Methods. PubMed, Cochrane Library, ScienceDirect, Embase, CNKI, and Wanfang Databases were used to search for articles that met the inclusion criteria. Two researchers independently screened the articles that met the inclusion criteria. RevMan 5.3 and STATA 16.0 were used for data analysis. This meta-analysis was registered at INPLASY with reference number ID: INPLASY202150017. Results. Thirteen eligible studies were selected, including 405 rats. The sources of stem cells are divided into four main categories: bone marrow mesenchymal stem cells (BMSCs), adipose-derived stem cells (ADSCs), amniotic membrane mesenchymal stem cells (AM-MSCs), and human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs). Compared with the OVX group, both stem cell transplantation groups had higher bone mineral density (BMD) (BMSCs: SMD=2.01, 95% CI: [1.38, 2.63], P<0.001, I2=76.6%; ADSCs: SMD=2.24, 95% CI: [0.79, 3.69], P=0.003, I2=86.7%) and bone volume/total volume (BV/TV) (hUCB-MSCs: SMD=1.71, 95% CI: [0.97, 2.44], P<0.001, I2=0%; ADSCs: SMD=2.16, 95% CI: [0.27, 4.04], P=0.025, I2=82.6%). In the BMSC treatment groups, the trabecular numbers (Tb.N) (SMD=4.28, 95% CI: [0.91, 7.64], P=0.013, I2=94.9%) were significantly higher, whereas the results for trabecular thickness (Tb.Th) (SMD=2.7, 95% CI: [-0.34, 5.73], P=0.081, I2=95.4%) and trabecular spacing (Tb.Sp) (SMD=−3.08, 95% CI: [-6.55, 0.38], P=0.081, I2=96.3%) were not statistically significant compared to those of the OVX group. The stem cell transplantation group had a low BMD, BV/TV, and Tb.N compared to the sham operation group. Conclusion. Stem cell therapy may increase bone strength, bone volume, and the number of trabeculae in OVX osteoporotic rats. The results of this meta-analysis showed the potential therapeutic effect of stem cell transplantation in OVX osteoporotic rats, bringing new therapeutic ideas and directions to the clinical treatment of osteoporosis. Due to the limited number and quality of studies related to some outcomes, more high-quality RCTs are still needed in the future to complement the existing findings.